A Picture Is Worth… Both Spelling and Sound - Coch, Donna (Frontiers in Psychology, 2018)
In an event-related potential (ERP) study using picture stimuli, we explored whether spelling information is co-activated with sound information even when neither type of information is explicitly provided. Pairs of picture stimuli presented in a rhyming paradigm were varied by both phonology (the two images in a pair had either rhyming, e.g., boat and goat, or nonrhyming, e.g., boat and cane, labels) and orthography (rhyming image pairs had labels that were either spelled the same, e.g., boat and goat, or not spelled the same, e.g., brain and cane). Electrophysiological picture rhyming (sound) effects were evident in terms of both N400/N450 and late effect amplitude: Nonrhyming images elicited more negative waves than rhyming images. Remarkably, the magnitude of the late ERP rhyming effect was modulated by spelling – even though words were neither explicitly seen nor heard during the task. Moreover, both the N400/N450 and late rhyming effects in the spelled-the-same (orthographically-matched) condition were larger in the group with higher scores (by median split) on a standardized measure of sound awareness. Overall, the findings show concomitant meaning (semantic), sound (phonological), and spelling (orthographic) activation for picture processing in a rhyming paradigm, especially in young adults with better reading skills. Not outwardly lexical but nonetheless modulated by reading skill, electrophysiological picture rhyming effects may be useful for exploring co-activation in children with dyslexia.